A Case Study on B-Tree Database Indexing Technique - A. Mostafa, Salama (Journal of Soft Computing and Data Mining, 2020)
In the last three decades, many organizations of various natures are used relational databases like health, education, businesses and in several applications. Human started collection information before computer system was designed. Presently, the data that collected by human in computer system named database system. The larger database the more number of joins will occur which ultimately leads to the increase in query retrieval time. This research is to implement a b-tree indexing technique on PostgreSQL database. The main objective of this paper is to implement and analyze the application of b-tree in database indexing technique. This case study may be useful for future research in developing new indexing techniques which will added new techniques together with existing techniques as to increase performance of the data query.